The self-confident parent [videorecording] - Guarendi, Raymund Ph.D. (Pasay City Reproduced by Daughters of St. Paul, 1996)
Packed with humor and real life examples, this presentation will encourage a positive view of parenting.
Part I. The right way myth. -- Part II. The Discipline myth. -- Part III. It's all right to be wrong.
VHS.
Keywords: Parenting